2021
DOI: 10.1101/2021.01.05.425331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interferon alpha-based combinations suppress SARS-CoV-2 infection in vitro and in vivo

Abstract: There is an urgent need for new antivirals with powerful therapeutic potential and tolerable side effects. In the present study, we found that recombinant human interferon-alpha (IFNa) triggered cell intrinsic and extrinsic antiviral responses and reduced replication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in human lung epithelial Calu-3 cells. However, IFNa alone was insufficient to completely abolish SARS-CoV-2 replication. Combinations of IFNa with camostat, remdesivir, EIDD-2801, cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…To test our hypothesis, we first analyzed toxicity and efficacy of Pegasys (pegylated IFNα) and nafamostat, against mCherry-expressing SARS-CoV-2 [20] in human lung epithelial Calu-3 cells using fluorescence and cell viability assay as readouts as described previously [11]. We observed that both Pegasys and nafamostat reduced SARS-CoV-2-mediated mCherry expression and rescued cells from virus-mediated death (Figure 1a).…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…To test our hypothesis, we first analyzed toxicity and efficacy of Pegasys (pegylated IFNα) and nafamostat, against mCherry-expressing SARS-CoV-2 [20] in human lung epithelial Calu-3 cells using fluorescence and cell viability assay as readouts as described previously [11]. We observed that both Pegasys and nafamostat reduced SARS-CoV-2-mediated mCherry expression and rescued cells from virus-mediated death (Figure 1a).…”
Section: Resultsmentioning
confidence: 75%
“…However, more targeted studies are needed to support the proposed mechanism of synergy. Our recent transcriptomics analysis revealed that IFNα activates transcription of many genes including endothelial plasminogen activator inhibitor (SERPINE1) in Calu-3 cells and human lung organoids [11]. Serpin E1 inhibits urokinase-type and tissue-type plasminogen activators (uPA and tPA) as well as various membrane-anchored serine proteases including transmembrane protease serine 2 (TMPRSS2) [21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synergistic drug pairs that do not involve a polymerase inhibitor have also been identified in Vero E6 cells, including nelfinavir plus amodiaquine ( 71 ), arbidol plus nitazoxanide ( 73 ), nitazoxanide plus emetine ( 73 ), and nelfinavir plus cepharanthine ( 78 ). Additional non-polymerase-targeted pairs found synergistic in Calu3 cells were interferon alpha plus camostat ( 86 ), interferon alpha plus nafamostat ( 96 ), and apilimod plus camostat ( 103 ). Interferon alpha plus nafamostat reduced viral loads in hamsters to a greater extent than the individual component drugs ( 96 ).…”
Section: Current Progress On Drug Combinations Against Sars-cov-2mentioning
confidence: 99%